1,4-Bis(pyrimidin-2-ylsulfanyl)butane - Akbar, M.; Quereshi, F.A.; Nasir, W.; Adnan, A.; Ng, S.W. (International Union of Crystallography, 2010)
The -SCH2CH2CH2CH2S- portion of the title compound, C12H14N2S2, adopts an extended zigzag conformation. The angles at the tetrahedral carbon atoms are marginally increased [113.63 (12)degrees and 111.38 (17)degrees for S-C-C and C-C-C respectively] from the idealized tetrahedral angle. The molecule lies on an inversion center located at the midpoint of the butyl chain. In the crystal, there is a pi-pi stacking interaction between inversion-related pyrimidine rings with mean interplanar spacing of 3.494 (2) angstrom.